PERANAN INDUSTRI KAYU LAPIS TERHADAP KESEMPATAN KERJA DAN PEMBANGUNAN WILAYAH KABUPATEN SIAK PROVINSI RIAU - Junaidi, Junaidi (Wahana Forestra: Jurnal Kehutanan, 2016)
The plywood industry is an asset Siak district government, especially in terms of employment and as a source of income. The plywood industry in Siak absorb a workforce of about 13 169 inhabitants and about 82% of that amount is the local workforce. Plywood contribution to regional revenue of about 4 billion per year, accounted for about 0.8% of GDP Siak. The plywood industry in Siak an activity base with more than one value LQ (LQ = 1.16), thus the greater the activity of the plywood industry as a sector basis in these areas, the greater the flow of revenue to the district of Siak. Keyword : sector base, plywood industry, coefficient of specialization.